Reading History with the Essenes of Elmira - Kreps, Anne (International journal for the study of new religions, 2018)
This article studies a modern Essene movement based in the United States for its unusual merging of New Age practice with Christian fundamentalism with ancient history. By harkening back to the mystical religions of the ancient Mediterranean, these modern Essenes are able to engage in syncretistic practices while claiming to preserve the traditions of the ancient Essenes.